Lexico-stylistic peculiarities of the English blog discourse (on the material of the author’s blog) - Morgunova Marina Nikolaevna; Chashko Marina Mikhailovna (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2015)
The article studies the lexical-stylistic features of English-language blogging discourse. The analysis was conducted on the material of blogs copyright texts known to media people, journalists and bloggers on various issues of environmental, social, cultural, political and economic spheres of society, selected the most discussed topics of the last two years (20142015). A comparative analysis of the blog with other forms of Internet communication (email, chat, twitter) is carried out. It is argued that blogs have a socio-transforming, democratizing potential, a special way of selfexpression, self-improvement and personal statement of uniqueness. Extralinguistic features of blog largely dictate its linguistic and stylistic characteristics. It is argued that the author’s blog - a kind of creative space for the personal development of the author’s ideas of creation, which determines the structure, design and content of the blog, as well as using linguistic means and stylistic devices that would most clearly reflect the purpose and theme of the blog. Selection of the lexical and stylistic means of the blog is determined by a combination of various determinants of the general and specific. It is revealed the use of Internet language, professionally-oriented vocabulary of various functional and stylistic status, stylistically marked vocabulary. Among the stylistic figures most common are a metaphor, simile, hyperbole epithet.